Design of Signal Integrality Simulation in High-speed Digital Circuit for DTECS - HOU Chun-yang; LI Long; ZHANG Yong-wei; SHI Li (机车电传动)
In order to enhance hardware reliability of distribute train electric control system, the signal integrity problems of high-speed digital circuit was simulated and studied. Simulation methods and tools were introduced, and with an example of DDR circuit, signal integrity simulation analysis of wave, matched resistance, crosstalk, and switching noise were discussed in detail. The simulation results and the test results were consistent which verified the reliability of the methods.